Implementation Sharia of Marketing in Islamic Concept - Abdullah, Ratna; Wahab, Abdul; Hamid Habbe, Abdul (Dinasti International Journal of Economics, Finance & Accounting, 2021)
Spiritual marketing concept of Islamic Banks, Spiritual marketing is a form of marketing that is imbued with spiritual values ??in all processes and transactions, until it reaches a level where all major stakeholders in all businesses (customers, employees and shareholders), suppliers, distributors and even competitors even if you find happiness, Therefore,This study aims to examine the implementation of Islamic marketing in Islamic concepts in Islamic banks.The data collection method in this article is a literature study by collecting information that is relevant to the topic or problem that will be or is being researched. With qualitative research, it is necessary to do descriptive analysis.The implementation of the concept of Islamic ethics in marketing marketing personnel at Islamic Banks was found to have been carried out completely. There are four characteristics of Islamic marketing, namely: Theistic (Rabbaniyah), Ethical (Aklaqiyyah), Realistic (Al-waqi'iyyah) and Humanistic (Al-Insaniyyah). In practice, marketing activities carried out by Islamic Banks are based on existing rules and do not conflict with Sharia principles. Five characteristics that must be possessed by a Sharia bank marketer are Shiddiq (True and Honest), Amanah, Fathanah (intelligent), Thabligh (communicative) and Istiqamah.